(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The telephone plays a central role in films, from social, linguistic and performative standpoints. At a basic level, it was portrayed as a status symbol in the 1930s Italian comedies, in the genre defined as Telefoni bianchi. From a linguistic viewpoint, the telephone was used - and it still is - as a metaphor of communication drawbacks and as a filter between reality and its reproductions. The analysis of Fellini’s La dolce vita shows many examples of this use: the telephone, as well as the tape-recorder, radio, television and cinema, takes part to the chaos of communication in the Rome-Babel represented in the film. The performative function is at stake when phone calls are employed as glosses, useful to introduce elements to provide further clarification for the audience. Thanks to information, which is often repeated in phone calls, authors disclose relevant elements of the story for the viewers, and in so doing, the telephone is a crucial factor which enables the suppression of redundant, useless and expensive characters or scenes.